The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00213-004-2122-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of citalopram in olfactory bulbectomy rats restores brain 5-HT synthesis rates: an autoradiographic study

Abstract: There is no significant global or individual structure difference in the synthesis between the Sham-CTP and OBX-CTP groups. The similarity in the synthesis between the OBX-CTP, Sham-CTP and Sham-SAL groups is likely a result of changes in the sensitivity of the receptors through which 5-HT synthesis is controlled. Because of some of the differences in the synthesis between the Sham-CTP and Sham-SAL groups, the data suggest that receptors throughout the brain are not fully desensitized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…We have shown that elevated 5-HT synthesis rates in an animal model of depression, olfactory bulbectomized (OBX) rats, were normalized following chronic SSRI treatment [30]. It was thought that normalized 5-HT synthesis rates resulted in the desensitization of the 5-HT 1A receptor [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that elevated 5-HT synthesis rates in an animal model of depression, olfactory bulbectomized (OBX) rats, were normalized following chronic SSRI treatment [30]. It was thought that normalized 5-HT synthesis rates resulted in the desensitization of the 5-HT 1A receptor [30].…”
Section: Discussionmentioning
confidence: 99%
“…A set of representative autoradiograms illustrating 5-HT synthesis in the rat brain as determined by the α-MTrp method have been presented in many previous publications [49,37,24,52,75,30,31] and their addition would not provide any new information, because the logarithmic scale between the tracer concentration (represented by 5-HT synthesis) and optical density. All that can be seen from these images is the brain non-homogenous distribution.…”
Section: Measurement Of the α-Mtrp Trapping And Calculation Of 5-ht Smentioning
confidence: 99%
See 2 more Smart Citations
“…Several neurochemical and behavioural studies [3][4][5] have found alterations in serotonergic neurotransmission after treatment with various classes of antidepressant drugs, including selective serotonin (5-hydroxytryptamine, 5-HT) reuptake inhibitors (SSRI), such as fluvoxamine [6].…”
Section: Introductionmentioning
confidence: 99%